Opposite effects of two different strains of equine herpesvirus 1 infection on cytoskeleton composition in equine dermal ED and African green monkey kidney Vero cell lines: application of scanning cytometry and confocal-microscopy-based image analysis in a quantitative study - Turowska, A; Pajak, B; Godlewski, M. M; Dzieciątkowski, T; Chmielewska, A; Tucholska, A; Banbura, M (Archives of virology, 2010)
Viruses can reorganize the cytoskeleton and restructure the host cell transport machinery. During infection viruses use different cellular cues and signals to enlist the cytoskeleton for their mission. However, each virus specifically affects the cytoskeleton structure. Thus, the aim of our study was to investigate the cytoskeletal changes in homologous equine dermal (ED) and heterologous Vero cell lines infected with either equine herpesvirus 1 (EHV-1) strain Rac-H or Jan-E. We found that Rac-H strain disrupted actin fibers and reduced F-actin level in ED cells, whereas the virus did not influence Vero cell cytoskeleton. Conversely, the Jan-E strain induced polymerization of both F-actin and MT in Vero cells, but not in ED cells. Confocal-microscopy analysis revealed that α-tubulin colocalized with viral antigen in ED cells infected with either Rac-H or Jan-E viruses. Alterations in F-actin and α-tubulin were evaluated by confocal microscopy, Microimage analysis and scanning cytometry. This unique combination allowed precise interpretation of confocal-based images showing the cellular events induced by EHV-1. We conclude that examination of viral-induced pathogenic effects in species specific cell lines is more symptomatic than in heterologous cell lines.